The Contribution of Competence and Work Motivation to The Performance of Posyandu Cadres in Adapting to The New Normal in Madiun City - Yunie Ernawati; Yuly Peristiowati; Agusta Dian Ellina (Journal Research of Social Science, Economics, and Management, 2023)
In adapting to new habits, every activity carried out by gathering the community must be carried out with due observance of the applicable health protocols, including service activities at Posyandu. The purpose of this study was to analyze the influence of the contribution of competence and work motivation on the performance of posyandu cadres in adapting to new habits in Madiun City. The design of this research is a quantitative observational study with a cross-sectional approach with a research focus directed at analyzing the effect of the contribution of competence and work motivation on the performance of posyandu cadres in adapting to new habits in Madiun City. Total population of 1444 respondents and a sample of 314 respondents were taken by Simple Random Sampling technique. The findings showed that the majority of respondents had sufficient category of work competency, 174 respondents (55.4%). Most of the respondents had medium category work motivation as many as 165 respondents (52.5%). Half of the respondents have sufficient category performance as many as 157 respondents (50.0%). Based on the results of the Multiple Linear Regression analysis, it shows that with a p-value of 0.000 <0.05, H1 is accepted, so it can be concluded that simultaneously there is an influence of competence contribution and work motivation on the performance of posyandu cadres in adapting to new habits in Madiun City with an influence magnitude of 70.2 %.